Indigenous kinship, colonial texts, and the contested space of early New England - Taylor, Marie Balsley, 1981- (Native Americans of the Northeast., 2023)
"New England history often treats Indigenous people as minor or secondary actors within the larger colonial story. Focusing on those Native Americans who were sachems, or leaders, in local tribes when Europeans began arriving, Marie Balsley Taylor reframes stories of Indigenous and British interactions and illuminates the vital role that Indigenous kinship and diplomacy played in shaping the textual production of English colonial settlers in New England from the 1630s until King Philip's War. Taylor argues that genres like the conversion narrative, the post-sermon question and answer session, and scientific treatise--despite being written in English for European audiences--were jointly created by Indigenous sachems and settlers to facilitate interaction within the contested space of colonial New England. Analyzing the writings of Thomas Shepard, John Eliot, John Winthrop Jr., and Daniel Gookin and the relationships these English Protestants formed with Indigenous leaders like Wequash, Cutshamekin, Cassacinamon, and Waban, this innovative study offers a new approach to early American literature--indicating that Native thought and culture played a profound role in shaping the words and deeds of colonial writers"--